Heart tumors - classification, diagnosis and methods of treatment - Adriana Misiło; Krzysztof Olczyk; Monika Sosna; Krzysztof Mordoń (Kazimierz Wielki University, 2023)
Heart tumors are a rare oncological problem. Nevertheless, they are an important element of cardio-oncology that should not be forgotten. The development of imaging techniques has made it possible to increase the probability of making a diagnosis in a non-invasive way. Despite the development of techniques such as computed tomography, magnetic resonance imaging or positron emission tomography, histopathological examination still remains the gold standard for making the final diagnosis and determining the appropriate therapeutic procedure. This paper is a summary of the available knowledge on the symptoms, diagnosis and treatment options of cardiac tumors. Data were obtained from PubMed and Google Scholar.